DETERMINANTS AFFECTING CUSTOMERS’ CONTINUANCE INTENTION OF USING INDIHOME AS INTERNET SERVICE PROVIDER IN MANADO - Reo, Alrick j.; Tulung, Joy E.; Pandowo, Merinda H.C. (Universitas Sam Ratulangi, 2021)
All individuals need technology to accelerate development or enhance individual and group development. Currently, one of technology that is growing very rapidly is internet technology. Indonesia is currently ranked in the world’s top three in the growth of world internet penetration. The rapid development of the internet in Indonesia was triggered by the needs of the Indonesian people towards the ease of obtaining information via the internet. The rapid growth of internet users has driven the growth of internet service providers. Internet service providers (ISP) is companies or entities that provide connection services and related services. One of the big ISP companies in Indonesia, which is widely used by the public today is Indonesia Digital Home (IndiHome). The purpose of this study is researcher want to analyse the determinants that affecting customers’ continuance intention of using IndiHome as internet service provider in Manado. In order to measure the tendencies for costumers to continuously renew their subscription (Continuance Intention), the research uses Perceived Usefulness and Perceived Ease of Use as the independent variables. The Result shows that both independent variables do have significant relevancies towards Continuance Intention of the Customers. Keywords: continuance intention, perceived ease of use, perceived usefulness, indihome